Effect of acids types on the recycling of used lubricating oil: article - Azmi, Nurul Nadhirah; Veny, Harumi; Tan, Huey Ling (2017)
The recycle of used lubricating oil by acid treatment is investigated. In this research, several types of acid were used such as nitric acid, hydrochloric acid, and Sulphuric acid. Two parameters measured which different types of acids and various concentrations of acid. This research is focused mostly on gaining a high-quality production of oil from used lubricating oil by treatment with acid as an addition to distillation process. The characteristic and quality of the treated lubricating oil is compared with the base oil by several parameters such as pour point, cloud point, dynamic viscosity, kinematic viscosity specific gravity and ash content. Initially, the used lubricating oil is filtered to remove the all the dirt. Then, gasoline is added to used lubricating oil following centrifugation at 1500 rpm for 10 minutes. The atmospheric distillation was conducted for the complete removal of water and gasoline. Finally, the lubricating oil is treated with the acids (nitric acid, hydrochloric acid, and Sulphuric acid) and neutralize with 6% of sodium hydroxide then separated by using settling and centrifuging the supernatant oil to remove remaining suspended solid. The result from the analysis showed that the kinematic viscosity for used lubricating oil is increase from 61.6034 Mm2 /s for used lubricating oil to 70.3862 Mm2 /s for Nitric acid treatment,73.9876 Mm2 /s for sulphuric acid treatment and 70.6906 Mm2 /s with for hydrochloric acid. The specific gravity decreases from 0.92 g/cm3 for used lubricating oil to 0.86 g/cm3 for nitric acid treatment,0.88 g/cm3 for sulphuric acid treatment and 0.84 g/cm3 with hydrochloric acid treatment. Other result from different analysis showed that the improvement and the best result is lubricating oil that treated with sulphuric acid which nearly like fresh lubricating oil. For different acid concentration, the lubricating oil that treated with 20% of sulphuric acid shows the best result in reduce contaminant within the used lubricating oil.